Presumed dangerous: punishment, responsibility and preventive detention in American jurisprudence - Corrado, Michael Louis (Carolina Academic Press, 2013)
Bail -- Detaining the insane : the legislatures and the courts -- Post-sentence preventive detention -- Undesirable aliens : Zadvydas (2001) -- Terrorists and unlawful combatants